2022
DOI: 10.1021/acs.orglett.2c00103
|View full text |Cite
|
Sign up to set email alerts
|

Iridium(III)-Catalyzed B(4)-Acylmethylation and B(3,5)-Diacylmethylation from o-Carboranes and Sulfoxonium Ylides

Abstract: An iridium(III)-catalyzed regioselective acylmethylation of the cage B(4)−H bond in o-carborane acids with sulfoxonium ylides is demonstrated through B(4)−H activation in ethanol under very mild conditions, affording a number of B(4)acylmethylated o-carboranes. Additionally, the selective sequential B(4)-and B(6)-acylmethylation reactions finally gave B(3,5)diacylmethylated o-carboranes in one pot.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 56 publications
0
10
0
Order By: Relevance
“…The works from our laboratory and Lee’s group showed that new cage B–C bonds can be formed via the insertion of carbene into the Ir–B­(cage) bond . We wondered whether a new cage B–N bond would be constructed by the insertion of nitrene into the cage B–Ir bond as anthranils are known precursors for nitrenes .…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The works from our laboratory and Lee’s group showed that new cage B–C bonds can be formed via the insertion of carbene into the Ir–B­(cage) bond . We wondered whether a new cage B–N bond would be constructed by the insertion of nitrene into the cage B–Ir bond as anthranils are known precursors for nitrenes .…”
mentioning
confidence: 99%
“…On the basis of the experimental results and the literature, ,, a proposed reaction pathway is presented in Scheme . Active cationic Ir­(III) catalyst A was generated via mixing [Cp*IrCl 2 ] 2 , AgNTf 2 , and KOAc.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, the unique spherical morphology of carboranes renders efficient derivatizations challenging, limiting their use. The establishment of efficient synthetic approaches for the regioselective functionalization of carboranes is necessary to realize the full potential of these unique compounds . Generally, functionalization of cage boron is more attractive than that of cage carbon because of the regioselectivity control among 10 cage B–H bonds compared with only two cage C–H bonds.…”
mentioning
confidence: 99%
“…Generally, functionalization of cage boron is more attractive than that of cage carbon because of the regioselectivity control among 10 cage B–H bonds compared with only two cage C–H bonds. Additionally, the carborane B–H proton is less acidic than the C–H (p K a ∼ 23), making the B–H bond activation followed by carborane functionalization more difficult than C–H bond activation and functionalization . In this context, the selective introduction of an allenyl group, capable of further functionalization onto o -carborane, is attractive.…”
mentioning
confidence: 99%